Moving Past Recent Turmoil: What is Becoming of the UK's Financial Services? - Bernard Offerlé (Revue LISA)
The paper looks at the impact of the latest economic crises on the UK’s financial services. It first describes the financial industry’s oversized contribution to Britain’s GDP and states what constraints and challenges the current situation poses in the short to medium term. The study moves on to review the various reform plans and official reports and it explains the different issues raised by new regulation in the wider EU context. The conclusion attempts to establish the distinction between what changes have actually been made and what remains mere politicking. The closing remarks call for further research embracing the other leading world financial centres.